2016
DOI: 10.1186/s12941-016-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety profile of linezolid in the treatment of multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis: a systematic review and meta-analysis

Abstract: BackgroundTreatment options for drug-resistant tuberculosis are still limited. Linezolid has been recommended for treatment of patients with multidrug-resistant (MDR) or extensively-drug-resistant (XDR) tuberculosis, although uncertainties remain regarding its safety and tolerability in these circumstances.ObjectiveTo systematically evaluate the existing evidence regarding the efficacy and tolerability of linezolid in the treatment of MDR or XDR tuberculosis.MethodsWe conducted a systematic review and meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 44 publications
(127 reference statements)
4
78
2
Order By: Relevance
“…This could be especially valuable in preventing toxicity among patients who are experiencing drug overexposure and in preventing therapeutic failure among patients who are experiencing drug underexposure . TDM might be of utmost importance for preventing drug‐related toxicity during long‐term treatment with linezolid, as, for example, for prosthetic and/or bone and joint infections and/or for MDR tuberculosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be especially valuable in preventing toxicity among patients who are experiencing drug overexposure and in preventing therapeutic failure among patients who are experiencing drug underexposure . TDM might be of utmost importance for preventing drug‐related toxicity during long‐term treatment with linezolid, as, for example, for prosthetic and/or bone and joint infections and/or for MDR tuberculosis .…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid is an oxazolidinone antibiotic with time‐dependent activity, which is licensed at the conventional dose of 600 mg every 12 hr for the treatment of pneumonia and of skin and soft tissue infections due to Gram positives . Nowadays, the use of linezolid in daily clinical practice has been widened to include the treatment for other difficult infections, such as prosthetic and bone and joint infections, and multi‐drug resistant (MDR) tuberculosis . This has posed some safety concerns, considering that the duration of treatment is restricted to 28 days maximum due to the risk of drug‐related adverse events .…”
mentioning
confidence: 99%
“…Linezolid is now being used for treatment of X/MDR-TB in adult patients (35). Salvage therapy studies demonstrated a striking sterilizing effect rate of linezolid as virtual monotherapy; negative sputum cultures were encountered as early as 2 weeks in some patients and at a median of 2.5 months in all patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…Although the global acquisition of tuberculosis infections has decreased by 1.5% per year [4,5], the progression of increased resistance of Mycobacterium tuberculosis (Mtb), as a consequence of prolonged and problematic therapeutic regimens, threatens the progress that has been made since 1990 in the control and prevention of TB [5]. Although the efficacy of the repurposed and newly recommended antibiotic for resistant forms of Mtb—Linezolid—has been recently evaluated from data provided by 23 studies in 14 different countries, involving more than 500 patients, suggests an overall success rate of 77% [6], the drug is notorious for producing a plethora of serious side effects such as neuropathy and hematological disorders [7]. Other newly approved drugs for MDR and XDR-TB therapeutics—bedaquiline and delamalid—are following the same path with their recognized efficacy against resistant forms of TB being threatened by their market cost and cumulative reports of side effects and lack of safety [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other newly approved drugs for MDR and XDR-TB therapeutics—bedaquiline and delamalid—are following the same path with their recognized efficacy against resistant forms of TB being threatened by their market cost and cumulative reports of side effects and lack of safety [8]. Despite the occurrence of these side effects, in the absence of better forms of effective therapeutic regimens, the World Health Organization (WHO) continues to recommend the use of these extremely costly drugs for therapy of MDR and XDR-TB [4,6,8]. But is there an inexpensive drug, in comparison to the cost of these drugs, that has been extensively studied and has been safely used for the therapy of psychosis for over 50 years producing no serious side effects if the patient are monitored properly?…”
Section: Introductionmentioning
confidence: 99%